2019
DOI: 10.3389/fgene.2019.00264
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Disease Resistance Against White Spot Syndrome Virus (WSSV) in Liptopenaeus vannamei

Abstract: White Spot Syndrome Virus (WSSV) is the most damaging pathogen in terms of production and economic losses for the shrimp sector world-wide. Estimation of heritability for WSSV resistance was made in this study to obtain necessary parameter inputs for broadening the breeding objectives of an ongoing selective breeding programme for Whiteleg shrimp ( Liptopenaeus vannamei ) that has focussed exclusively on improving growth performance since 2014. The present study involved a disease challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
0
38
1
4
Order By: Relevance
“…The data suggested Nimav-1_LVa virus might take a different strategy than WSSV, aiming at a long-term or benign relationship with the host. The genome of Nimav-1_LVa could facilitate a better understanding of evolution in virus family Nimaviridae and could also be applicable in the shrimp breeding, traceability of farmed shrimp, WSSV diagnosis, and treatment of WSD [26,87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data suggested Nimav-1_LVa virus might take a different strategy than WSSV, aiming at a long-term or benign relationship with the host. The genome of Nimav-1_LVa could facilitate a better understanding of evolution in virus family Nimaviridae and could also be applicable in the shrimp breeding, traceability of farmed shrimp, WSSV diagnosis, and treatment of WSD [26,87].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Kuruma shrimp, Penaeus (Marsupenaeus) japonicus, illustrated that the entry of WSSV into the host cell is via the endocytosis pathway, triggered by the interaction of virion and a transmembrane immunoglobulin receptor, designated as MjpIgR [24]. So far, progress has been made in developing WSSV-resistant P. vannamei lines [25,26], but a lot more work remains ahead to achieve the stabilization of the resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, heritability of disease resistance is observed without negatively influencing animal growth [ 187 ], such as has been observed in rainbow trout with resistance towards F. psychrophilum [ 188 ] or F. columnare [ 189 ]. However, it has also been shown that selecting for resistance to a single pathogen can sometimes result in increased susceptibility to another or in decreased growth [ 190 , 191 , 192 , 193 , 194 ]. In these studies, the gold standard for determining disease resistance is survival comparisons during live infection challenges (reviewed in [ 195 ]).…”
Section: Current Methods Of Bacterial Disease Prevention In Aquacumentioning
confidence: 99%
“…Improved resistance to infectious diseases through selective breeding has been demonstrated in previous studies (Doan et al, 2017;Trang, Nguyen, Nguyen, Wayne, & Nguyen, 2019b). Across aquaculture species, heritabilities (h 2 ) for resistance to a range of diseases from parasites to bacteria and virus are low to moderate (Ødegård, Baranski, Gjerde, & Gjedrem, 2011), for instance, h 2 = 0.03 -0.18 for resistance to Aeromonas salmonicida bacteria in Atlantic salmon (Salmo salar) (Gjerde, Evensen, Bentsen, & Storset, 2009;Kjøglum, Henryon, Aasmundstad, & Korsgaard, 2008;Ødegård, Olesen, Gjerde, & Klemetsdal, 2006, 2007bOlesen, Hung, & Ødegård, 2007); h 2 = 0.05-0.25 for resistance to Yersinia ruckeri and Flavobacterium psychrophilum bacteria in rainbow trout (Oncorhynchus mykiss) (Evenhuis, Leeds, Marancik, Lapatra, & Wiens, 2015;Hastefnl, Guo'ding, & Eve-Risen, 2005;Leeds et al, 2010;Silverstein et al, 2009;Wiens et al, 2013); h 2 = 0.03 and 0.04 for resistance to Aeromonas hydrophila bacteria in Rohu carp (Labeo rohita) (Mahapatra et al, 2008) and in common carp (Cyprinus carpio) (Ødegård et al, 2010), respectively; or h 2 = 0.08 for resistance to Vibrio anguillarum in Atlantic cod (Kettunen, Serenius, & Fjalestad, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…However, there has not been any selection programme for improved resistance to S. iniae in Asian seabass. Furthermore, genetic association between disease resistance and growth or survival is not consistently reported in aquaculture species, being either positive (Barría, Doeschl-Wilson, Lhorente, Houston, & Yáñez, 2019), negative (Yáñez et al, 2016) or not significant (Trang, Nguyen, et al, 2019b). There is also a paucity of scientific knowledge regarding genetic relationships between disease resistance and cannibalism in aquaculture species, especially in marine finfish including seabass.…”
Section: Introductionmentioning
confidence: 99%